"Vacuum consolidation improves peat ground conditions" - O'Kelly, Brendan (My University, 2010)
Trinity College Dublin is currently testing an innovative technique, known as vacuum consolidation, to improve peat ground conditions, as part of the National Roads Authority Fellowship initiative.
PUBLISHED
One page News Feature on the TCD/NRA Vacuum Consolidation Field Trail at Ballydermot Bog reported in Construction & Property News Magazine
Keywords: Ground improvement; peat; Vacuum consolidation; Smart & Sustainable Planet; Civil Engineering, Pavements and Structures; Environmental aspects of transportation; Environmental engineering